Managing the Challenges facing Technical and Vocational Education Programme in Rivers State for National Cohesion and Global Competitiveness. - Ebete, Samuel Emeka; Ojude, Lawrence Chukwuwogbede; Akpelu, Frankline Ekwueme (NIU Journal of Social Sciences; Vol 5 No 4 (2019): KIU Journal of Social Sciences, Vol. 5 No. 4, December 2019, 2020)
The study investigated managing the challenges facing technical and vocational education programmes in Rivers State for national and global competitiveness. Three research questions and three corresponding hypotheses guided the study. The descriptive survey design was adopted. A sample size of 115 representing 30% was drawn from a population of 347 directors and principals, using stratified sampling technique. An instrument titled managing the challenges facing technical/vocational education questionnaire (MCFTVEQ) was used for data collection. Validity of the instrument was ascertained using professional critique of experts in educational management and evaluation. Reliability was obtained through test re-test method, using a sample of 20 selected vice principals in Rivers State who are not part of the study group. The instrument yielded a reliability index of 0.74. The mean and standard deviation were used to answer the research questions while the z-test was used to test the hypotheses at 0.05 significant level. The findings revealed that the challenges facing technical and vocational education in Rivers State are, inadequate finding, no equipped workshops and laboratories, strong dislike for the programme and brain drain. Technical and vocational education provides employable and productive skills, change negative attitudes and inculcate positive attitudes on the citizens that will bring national cohesion and global competitiveness. It was inter alia recommended that Rivers State government should provide fund to technical and vocational schools, ensure better remuneration for technical education teachers, embark on enlightenment campaign, provide workshops, ensure appropriate maintenance culture in technical and vocational school and provide collaboration between vocational schools and companies. Keywords: Technical, vocational, education cohesion, global competitiveness